Modeling the Winter–to–Summer Transition of Prokaryotic and Viral Abundance in the Arctic Ocean - Christian Winter (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Jérôme P. Payet (Department of Microbiology, Oregon State University); Curtis A. Suttle (Departments of Earth, Ocean and Atmospheric Sciences, Microbiology and Immunology, Botany, and the Biodiversity Research Centre, The University of British Columbia) (PLoS ONE, 2012)
The abstract is available here: https://uscholar.univie.ac.at/o:597979 The abstract is available here: https://uscholar.univie.ac.at/o:597979